2016
DOI: 10.1016/j.jdent.2016.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial effects of commensal oral species are regulated by environmental factors

Abstract: Identifying beneficial oral bacteria and understanding how they inhibit pathogens might help to unravel the mechanisms behind dysbiotic oral diseases. In this context, this study points towards an important role for hydrogen peroxide. The latter might lead in the future to novel preventive strategies for oral health based on improving the antimicrobial properties of commensal oral bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
97
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 87 publications
(108 citation statements)
references
References 61 publications
5
97
0
Order By: Relevance
“…It has been shown that some commensal species can suppress the growth of pathobionts by H 2 O 2 under specific environmental conditions. More specifically, the sequence of colonization and the presence of oxygen are major influencing factors11. Additionally, dysbiotic biofilms are enriched in virulence factors that stimulate the host inflammatory response21.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that some commensal species can suppress the growth of pathobionts by H 2 O 2 under specific environmental conditions. More specifically, the sequence of colonization and the presence of oxygen are major influencing factors11. Additionally, dysbiotic biofilms are enriched in virulence factors that stimulate the host inflammatory response21.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown clinically that in patients with periodontal disease, there is a decline in commensal streptococci such as Streptococcus sanguinis 810. It was suggested that H 2 O 2 is one of the most important antimicrobials produced by certain streptococci11. For instance, S. sanguinis and Streptococcus gordonii can inhibit the growth of Streptococcus mutans and Aggregatibacter actinomycetemcomitans by H 2 O 2 production1213.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A second strategy employed by oral commensal streptococci to achieve a competitive advantage over oral pathogens is the generation of hydrogen peroxide (H 2 O 2 ), which inhibits the growth of S. mutans , the periodontal pathogen Porphyromonas gingivalis (96), and other oral pathogens. Among the known peroxigenic commensals, which include S. oralis , S. mitis , S. sanguinis , S. gordonii and S. oligofermentans , there are multiple enzymatic pathways for the generation of H 2 O 2 .…”
Section: The Good Streptococci: Commensal Oral Floramentioning
confidence: 99%
“…13,1418 The inhibitory effect of H 2 O 2 extends also towards periodontal pathogens such as Aggregatibacter actinomycetemcomitans (Aa). 19 However, the interspecies interaction between Aa and Sg seems to be more intricate since non/lethal concentrations of H 2 O 2 favor survival of Aa against the host innate immunity by inducing a specific transcriptional response 20 tailored towards complement evasion. This indicates that the concentration of H 2 O 2 in the context of a biofilm determines its potential as antimicrobial or signaling component.…”
Section: Introductionmentioning
confidence: 99%